Testing the Performance of Leading Banks in India - An Experimental Study - Dharmaraj, C.; Samuel Joseph, C.; Santhosh, Esme (Indian Journal of Finance, 2011)
This study tests the performance of leading banks of India during the financial year 2008-2009. The year 2008-2009 was chosen as this year faced the greatest financial crisis in the human history. The banks selected for study are the top ten banks rated as per the Business today KPMG survey and includes Axis Bank, Bank of India, Punjab National Bank, Bank of Baroda, HDFC bank, Indian Bank, Federal Bank, Corporation Bank, Union Bank of India and Citibank. Performance of these banks were tested with the help of eight performance parameters like Operating Profit , Net Interest Income, Cost to Income Ratio, Capital Adequacy Ratio, Net NPA’s, Deposit growth, Return on Assets and Return on Capital Employed. This study helps to know the strength and weakness of each bank. It also sheds light on the performance of the Indian Banking Industry during financial recession.